Genotypic variation for normalized difference vegetation index and its relationship with grain yield in wheat under terminal heat stress - Ramya, K.T.; Jain, N.; Ramya, P.; Singh, P.K.; Arora, A.; Singh, G.P.; Prabhu, K.V. (The Indian Journal of Genetics and Plant Breeding, 2016)
The present study was conducted to determine genotypic variations for normalized difference vegetation index (NDVI) at eight different growth stages and its relationship to yield in wheat under terminal heat stress. Thirty six wheat genotypes were evaluated under staggered sowing, timely sowing (15th November,normal),late sowing (15th December, heat stress) and very late sowing (6th January, heat stress) during 2012-13 and 2013-14. The NDVI was recorded at different growth stages viz., flag leaf, booting, heading, anthesis, milk dough, and maturity.The wheat genotypes differed significantly for NDVI at each stage and at each sowing condition. Rate of reduction in NDVI from heading to dough stage was low for genotypes namely, KAUZ/AA// KAUZ,SOKOLL,HW2004,HD2864, HD2967,FLW18,CHIRYA 7 and HD2932. Overall, under heat stress leaf senescence was 7 to 14 per cent faster than normal condition. Genotypes which maintained high NDVI were potential stress tolerant with higher stress tolerance index. Since data recording of NDVI is relatively easier than any other physiological traits, it could serve as indirect selection criteria to measure stress tolerance facilitating selection of the lines from large populations.